A framework for techno-economic assessment of demand-side power-to-heat solutions in low-temperature district heating. (November 2020) - Wang, Jiawei; Cai, Hanmin; You, Shi; Zong, Yi; Zhang, Cuo; Træholt, Chresten
Highlights: A novel framework for techno-economic assessment of power to heat solutions. Fuel shift control for electric heat boosters in low-temperature district heating. Framework is demonstrated and verified through valuable case studies Abstract: In this paper, technical and economic assessment of power-to-heat (P2H) solutions installed at the building side is presented. A framework solution including different control algorithms, network and operational parameters, is proposed to conduct techno-economic assessment for P2H technologies in low-temperature district heating (LTDH) from an integrated energy system perspective. The framework facilitates the transition from conventional DH to LTDH solution with demand-side P2H technologies. An electric heat booster (EHB), as a typical demand side P2H solution, is modelled with different control algorithms and tank sizes and applied to a 23 single-family test energy system. Steady state combined heat and power flow is studied to investigate the impact on networks. Moreover, minimum differential pressure and supply temperature control of critical nodes are applied to ensure reliable DH operation. The results show the effectiveness of fuel shift control, where the ratio of DH loss is decreased by lowering supply temperature to 50 ° C . Furthermore, the minimum voltage magnitude is improved to be closer to 1 p.u., meanwhile, the power loss on electricity networks is increased. For the test energy system, the 51 L EHBs contribute to lower energy cost of the system compared to the 92 L ones, and can provide the lowest levelized cost solution with the supply temperature of 50 ° C .